5(4z-1)-2(Z+2)=14(Z+1)

Simple and best practice solution for 5(4z-1)-2(Z+2)=14(Z+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(4z-1)-2(Z+2)=14(Z+1) equation:


Simplifying
5(4z + -1) + -2(Z + 2) = 14(Z + 1)

Reorder the terms:
5(-1 + 4z) + -2(Z + 2) = 14(Z + 1)
(-1 * 5 + 4z * 5) + -2(Z + 2) = 14(Z + 1)
(-5 + 20z) + -2(Z + 2) = 14(Z + 1)

Reorder the terms:
-5 + 20z + -2(2 + Z) = 14(Z + 1)
-5 + 20z + (2 * -2 + Z * -2) = 14(Z + 1)
-5 + 20z + (-4 + -2Z) = 14(Z + 1)

Reorder the terms:
-5 + -4 + -2Z + 20z = 14(Z + 1)

Combine like terms: -5 + -4 = -9
-9 + -2Z + 20z = 14(Z + 1)

Reorder the terms:
-9 + -2Z + 20z = 14(1 + Z)
-9 + -2Z + 20z = (1 * 14 + Z * 14)
-9 + -2Z + 20z = (14 + 14Z)

Solving
-9 + -2Z + 20z = 14 + 14Z

Solving for variable 'Z'.

Move all terms containing Z to the left, all other terms to the right.

Add '-14Z' to each side of the equation.
-9 + -2Z + -14Z + 20z = 14 + 14Z + -14Z

Combine like terms: -2Z + -14Z = -16Z
-9 + -16Z + 20z = 14 + 14Z + -14Z

Combine like terms: 14Z + -14Z = 0
-9 + -16Z + 20z = 14 + 0
-9 + -16Z + 20z = 14

Add '9' to each side of the equation.
-9 + -16Z + 9 + 20z = 14 + 9

Reorder the terms:
-9 + 9 + -16Z + 20z = 14 + 9

Combine like terms: -9 + 9 = 0
0 + -16Z + 20z = 14 + 9
-16Z + 20z = 14 + 9

Combine like terms: 14 + 9 = 23
-16Z + 20z = 23

Add '-20z' to each side of the equation.
-16Z + 20z + -20z = 23 + -20z

Combine like terms: 20z + -20z = 0
-16Z + 0 = 23 + -20z
-16Z = 23 + -20z

Divide each side by '-16'.
Z = -1.4375 + 1.25z

Simplifying
Z = -1.4375 + 1.25z

See similar equations:

| 2(x+8)-x=2(3-x)-7 | | (5x+1)[2]=7 | | (3x+1)(x+2)=-1 | | 3(5x+4)+5x=-8x | | 3x+6x=4x+9x | | 42x+37x^2-72x=46 | | x^2+10x+21=40 | | x+(x+34)=35 | | x^2+10x+21=12257001 | | x^2+10x+21=122500 | | x^2+10x+21=1225 | | x^2+10x+21=96 | | x^2+10x+21=1156 | | 5-12x+6x^2-x^3= | | x^2+10x+21=1089 | | x^2+10x+21=1024 | | x^2+10x+21=961 | | x^2+10x+21=900 | | x^2+10x+21=841 | | x^2+10x+21=784 | | x^2+10x+21=729 | | x^2+10x+21=676 | | x^2+10x+21=625 | | x^2+10x+21=576 | | x^2+10x+21=529 | | x^2+10x+21=484 | | x^2+10x+21=441 | | x^2+10x+21=400 | | 4x^2-72=0 | | x^2+10x+21=361 | | x^2+10x+21=324 | | x^2+10x+21=289 |

Equations solver categories